2004
DOI: 10.1038/sj.ejcn.1601853
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient adequacy and dietary diversity in rural Mali: association and determinants

Abstract: Objective: To examine the association between nutrient adequacy and dietary diversity, and to assess and compare the determinants for the two constructs in an adult population in rural Mali. Design: Cross-sectional study assessing food intake by a validated 7-day quantitative food frequency questionnaire. Two different dietary diversity indexes were created: food variety score (FVS), a simple count of food items, and diet diversity score (DDS) a count of food groups. Mean adequacy ratio, the mean ratio of inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
207
5
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(250 citation statements)
references
References 17 publications
21
207
5
8
Order By: Relevance
“…They reported that by increasing DDS, energy intake was also increased. Torheim et al (41) indicated a positive correlation between energy intake and DDS, as well as variety of different food groups in Mali. The results for Tehranian men were the same (19) .…”
Section: Discussionmentioning
confidence: 98%
“…They reported that by increasing DDS, energy intake was also increased. Torheim et al (41) indicated a positive correlation between energy intake and DDS, as well as variety of different food groups in Mali. The results for Tehranian men were the same (19) .…”
Section: Discussionmentioning
confidence: 98%
“…The links between biodiversity and dietary diversity at the household or individual levels, however, remain inconclusive. This is because some studies have reported no association [4144]. Results from a study in Tanzania show that at the bivariate data analysis level, dietary diversity was significantly and positively influenced by crop count but did not show a significant association with the Simpson’s Index which measures the number of crops as well as the distribution of area cultivated under various crops.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the overall nutritional quality as well as nutrient adequacy of the diet is improved with a (19) . diverse diet (27)(28)(29)(30) . DDS is a major element of a highquality diet as it represents the variety of the diet.…”
Section: Discussionmentioning
confidence: 99%